Citizen science-based jellyfish observation initiatives in the Mediterranean Sea - Dor Edelist; Antonio Canepa-Oneto; Joel Azzopardi; Ainara Ballesteros; Jesús Bellido; Ferdinando Boero; Cesar Bordehore; Alan Deidun; Eva S. Fonfría; Adam Gauci; Josep Maria Gili; Sonia K. M. Gueroun; et al. (Hydrobiologia, 2025)
We present Citizen Science-based Jellyfish Observation Initiatives (CS JOIs) across the Mediterranean Basin and propose a path toward standardization of the data they produce. We explored data collection and management through a shared database schema. Using an expert opinion questionnaire and adhering to standards that are recognized globally (e.g., by GBIF, OBIS, and EMODnet) such as Darwin Core and IOOS terminology, we propose a three-stage approach toward data management and standardization. JOIs vary in purpose, function, language, data collection, validation methodology, outreach, and levels of citizen engagement and training. This diversity presents unique opportunities and challenges for data collection and management. JOIs typically combine the dual role of providing real-time alert systems and enhancing our long-term knowledge of jellyfish distribution and, eventually, ecology. When global reporting systems are considered, local initiative identity, language, purpose, and community must be preserved to allow meaningful CS processes to evolve, while the integration of JOIs within them (and data collection and management in general) must be performed via standardized and shared methodologies. Finally, we discuss the contribution of novel technologies toward improving the activities and management of JOIs worldwide.

Plant distribution and conservation in mediterranean islands’ lentic wetlands: there is more than aquatic species - Mauro Fois; Alba Cuena-Lombraña; Mathieu Artufel; Vincent Attard; Salvatore Cambria; Krista Farrugia; Michela Marignani; Pietro Minissale; Andrea Pace; Saverio Sciandrello; Eva Tankovic; Gianluigi Bacchetta (Biodiversity and Conservation, 2024)
This study investigates the distribution and conservation status of plant species in lentic wetlands of Mediterranean islands. Field data on vascular macrophytes were collected from the online national databases of the “Conservation of the island wetlands of the Mediterranean Basin” (MedIsWet). A comprehensive inventory of wetlands was conducted, and information on the main anthropogenic impacts and conservation priorities was compiled. In addition to all vascular hygro- and hydrophytes, we retained information on those species typically adapted to environments with intermittent or temporary wetness. A significant knowledge gap regarding the distribution and conservation of plant species in Mediterranean wetlands was found. A lower endemism rate was observed particularly in coastal wetlands. However, approximately 25% of species, mainly with relatively wide distribution, were identified as endangered or with unknown conservation status. Including all macrophytes adapted to seasonal wetness is crucial when considering wetland conservation efforts. The research emphasised the importance of considering diverse wetland types, including seasonal and permanent, natural and artificial, for effective plant conservation. Artificial wetlands emerged as potential habitats with considerable biodiversity conservation value. This study provides a comprehensive inventory of wetlands and valuable insights into the distribution, ecology, and conservation relevance of aquatic macrophytes in Mediterranean islands. The research enhances our understanding of biogeographic patterns and processes, offers critical information for the management and conservation of Mediterranean island wetlands, and presents a replicable approach that can be applied to other wetland contexts.

The future for Mediterranean wetlands: 50 key issues and 50 important conservation research questions - Nigel G. Taylor; Patrick Grillas; Hazem Al Hreisha; Özge Balkız; Maud Borie; Olivier Boutron; Ana Catita; Jocelyn Champagnon; Semia Cherif; Kerim Çiçek; Luís T. Costa; Mohamed Dakki; et al. (Regional Environmental Change, 2021)